Penetration depth method-novel real-time strategy for evaluating femoroacetabular impingement - Arbabi, Ehsan; Chegini, Salman; Boulic, Ronan; Tannast, Moritz; Ferguson, Stephen J.; Thalmann, Daniel (Journal of orthopaedic research, 2010)
We introduce a new method for computerized real‐time evaluation of femoroacetabular impingement (FAI). In contrast to previously presented stress analyses, this method is based on two types of predictions of penetration depths for two rotating bodies: curvilinear and radial penetration depth. This intuitive method allows the analysis of both bony and soft tissue structures (such as cartilage and acetabular labrum) in real time. Characteristic penetration depth patterns were found for different subtypes of FAI, such as cam and pincer pathologies. In addition, correlation between the penetration depths (estimated by applying this method) and the existing contact stresses (estimated by applying the finite element method) of various hip morphologies were found. A strong correlation with predicted stress values existed, with a mean correlation coefficient of 0.91 for the curvilinear and 0.80 for the radial penetration method. The results show that the penetration depth method is a promising, fast, and accurate method for quantification and diagnosis of FAI. © 2010 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 28:880–886, 2010